Foundational Excellence: Theories for Modern Colorectal Surgery Education—Key Pedagogical Frameworks and Strategies that Every Colorectal Surgeon Teaching Medical Students, Residents, and Co-workers Should Know - Beaty, Jennifer S.; Cleary, Robert (Clinics in Colon and Rectal Surgery, 2025)
Quality modern colorectal surgery education demands more than simply teaching technical skills; it requires a deep understanding of how surgeons learn. This article explores foundational pedagogical theories that support effective instruction across all stages of surgical training. Cognitive load theory, behaviorist models, and constructivist approaches such as experiential and social learning are examined for their relevance to surgical education. Deliberate practice and mastery learning frameworks offer structured methods for developing procedural expertise. Teaching strategies such as simulation and feedback models are discussed to promote competence and autonomy. Additionally, the article considers emotional and motivational components of learning, highlighting the roles of self-efficacy, feedback, and reflective practice. By aligning educational practice with established theory, colorectal surgeons can more effectively train future colleagues and elevate standards of care, professionalism, and continuous learning in a dynamic healthcare landscape.
Keywords: surgical education; cognitive load theory; deliberate practice; colorectal surgery training